Neurogenic Tumors of the Mediastinum: A Report of 60 Cases - Salih Topçu; Aysin Alper; Erkmen Gülhan; Osman Koçyigit; Irfan Tastepe; Güven Çetin (Canadian Respiratory Journal)
OBJECTIVES: To analyze retrospectively 60 patients (13 infants and children, 47 adults - 21 men and 39 women) with mediastinal neurogenic tumours admitted to Atatürk Centre for Chest Disease and Chest Surgery, Ankara, Turkey between 1988 and 1999. This comprised 21.2% of 283 patients who had surgical operations for all mediastinal masses during the same period.